A molluscan class struggle: exploring the surprisingly uneven distribution of chemosymbiosis among two major mollusk groups - Hughes, Ian V.; Girguis, Peter R. (Frontiers in Marine Science, 2023)
Many bivalves and gastropods from marine reducing environments such as deep ocean hydrothermal vents and seeps host chemosynthetic bacteria in a nutritional symbiosis. Despite their functional similarities, the distribution of chemosymbiosis in these two mollusk classes is surprisingly uneven: the number of bivalve species known to host chemosynthetic symbionts is more than twenty times that of gastropods, and chemosymbiotic bivalves are reported from a far greater diversity of marine habitats. Here we explore the potential drivers for this trend, including but not limited to physiological differences, habitat characteristics, and sampling bias. Sampling bias likely contributes to the magnitude of the observed discrepancy, but we posit that the phenomenon itself reveals how intrinsic (e.g. morphology) and extrinsic (e.g. organic matter availability) factors might have shaped the distribution of extant gastropod and bivalve associations. These observations also serve as an impetus for increasing investigation into gastropods and other mollusks from chemically reducing environments to better understand the evolution and ecology of chemosymbiosis among molluscan hosts.